Prospective Investigation of Pesticide Applicators' Health (PIPAH) study: a cohort study of professional pesticide users in Great Britain. Issue 10 (10th October 2017) - Harding, Anne-Helen; Fox, David; Chen, Yiqun; Pearce, Neil; Fishwick, David; Frost, Gillian
Abstract : Purpose: The purpose of the study is to monitor the exposure and health of workers in Great Britain who use pesticides as a part of their job, and to gain a better understanding of the relationship between long-term exposure to pesticides and health. Participants: Study participants are professional pesticide users who are certified in the safe use of pesticides or who were born before 1965 and apply pesticides under 'grandfather rights'. Overall response rate was 20%; participants are mostly male (98%) and the average age is 54 years, ranging from 17 to over 80 years. Findings to date: Participants have completed a baseline general questionnaire and three follow-up questionnaires on the use of pesticides. These data will enable investigations into the relationship between occupational pesticide exposure and health outcomes taking into account non-occupational confounding factors. Future plans: There is no set end date for data collection. Recruitment into the cohort will continue, and for the foreseeable future there will be annual pesticide use questionnaires and five yearly follow-up general questionnaires. The intention is to validate the pesticide use questionnaire, and to develop a crop/job exposure matrix (C/JEM) which can be updated regularly. This C/JEM will be able to look at general categories of pesticide, such as insecticides, structurally related pesticides, such as organochlorines, or individual active ingredients. Data collected on use of personal protective equipment and method of application will provide information on how potential exposure to pesticide during application may have been modified. The study will be able to estimate changes in individual pesticide use over time, and to examine the associations between pesticide use and both baseline and long-term health outcomes. The cohort members will be linked to national databases for notification of hospital episode statistics, cancer incidence and mortality for follow-up of health outcomes.